2015
DOI: 10.1002/nme.5128
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic flow‐based particle splitting in smoothed particle hydrodynamics

Abstract: Summary In this work, a dynamic procedure for local particle refinement to be used in smoothed particle hydrodynamics (SPH) is presented. The algorithm is able to consistently produce successive levels of particle splitting in accordance to a flow‐based criterion. It has been applied together with accurate and robust formulations for variable spatial resolution in the framework of a semi‐implicit, truly incompressible scheme for SPH. Different test cases have been considered to assess the capabilities and adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Similar study was conducted to approximate the density jump presented in Equation (35). To start with, a total of 250 particles were placed equidistant from each other, between x D 0:5 to x D 0:5.…”
Section: Numerical Assessment Of the Skewed Kernel Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar study was conducted to approximate the density jump presented in Equation (35). To start with, a total of 250 particles were placed equidistant from each other, between x D 0:5 to x D 0:5.…”
Section: Numerical Assessment Of the Skewed Kernel Approachmentioning
confidence: 99%
“…A novel SPH method called the adaptive SPH with anisotropic tensor‐based adaptation was developed by Shapiro et al . An interesting method of adaptivity is the particle splitting, with several variants for particle refinement .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Feldman and Bonet [20] presented a particle splitting method for adaptive refinement in dynamic fluid problems and investigated numerical errors; Vacondio et al [21] introduced a variable-resolution technique by splitting a parent particle into child particles and vise versa for refinement and coarsening, respectively. Subsequently, a number of adaptive particle methods have been proposed on controlling the resolution in fluid problems [22,23,24,25,26]. However, those techniques often encounter a problem in conservation of mass [22] and generally require a cumbersome implementation with respect to a parallel computation.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the total mass did not always conserve during this process [7]. Khorasanizade and Sousa [8] presented a dynamic flow-based particle splitting method.…”
Section: Introductionmentioning
confidence: 99%
“…Since the refinement zone is static, the static resolution is not adaptive. In contrast, for dynamic resolution, the refinement zones move according to the physical properties of the flows, such as density [3], velocity [5], and vorticity [8]. The dynamic resolution method is partially adaptive because the refinement criteria based on density, velocity or vorticity need to be defined beforehand and are different for different cases.…”
Section: Introductionmentioning
confidence: 99%